Pergeseran Bahasa Enggano dalam Komunikasi Siswa SDN 053 Pulau Enggano Sebagai Literasi Bahasa Daerah - Wahyu Alfanda; Abdul Muktadir; Puspa Djuwita (UNIB Press, 2023)
This study aims to describe the shift in the Enggano language in the Indonesian language communication of SDN 053 Enggano Island students as regional language literacy. This type of research is qualitative research using a descriptive approach, the data used is qualitative data obtained from the results of interviews, observations, and observations which are then presented descriptively. Based on data analysis and research discussion, the conclusions that can be drawn from this study are: 1. Class IV teachers at SD Negeri 053 Enggano during the teaching and learning process, the form of communicating with students uses Indonesian, both delivering material and giving advice, this causes a shift in language the Enggano area into Indonesian. This factor resulted in the teaching and learning process not using the Enggano regional language so students get used to not using the Enggano regional language. 2. The form of globalization factor has a strong impact on the shift in regional languages ​​in Enggano, especially at SD Negeri 053 Enggano Island. This is due to the culture that enters and develops on Enggano Island 3. Efforts to preserve local languages ​​through education, especially basic education, have several functions, namely preventing shifts and extinction of regional languages, preparing local language speakers for the future, and preserving national culture.